The Study of AI integrated Simulation in Building Information Modelling (BIM) Use at Architectural Design Studio - Stephanus Wirawan Dharmatanna; Elvina Shanggrama Wijaya (Universitas Atma Jaya Yogyakarta, 2025)
The presence of Artificial Intelligence (AI) has been widely spread and used in many aspects of life, including education, as an image generator, source of data exploration, and means of visualization. Nevertheless, the research regarding the use of AI in the Architectural design studio process is still few, especially in the context of Indonesian Architectural education. Therefore, this research aims to picture the use of AI integrated Building Information Modelling in the design studio. This research was done by combining observation and a questionnaire. The use of AI in wind and thermal simulation of 5th-semester students with medium-rise building projects was studied. The students were being exposed to conventional simulation software, before being introduced to Autodesk Forma, an AI based cloud simulation. After the semester ends, students are asked to fill in a questionnaire regarding their process of doing simulation. The result is that most of the students find the AI-based simulation easy, regardless of the limitation of simulated areas and the maximum file size of the trial-free version. They still find more benefits of using the AI Simulation compared to conventional one, as they can reflect on their design and develop them according to the simulation results more effectively and holistically. Future studies regarding the use of AI in other design stages could be done as a follow-up to ensure the creativity of architectural design thinking.